The amphiregulin- epidermal growth factor receptor axis as a therapeutic target in sepsis - Walsh, Rebecca; Snow, Timothy Arthur Chandos; Martinez, Alexandra Z.; Brealey, David; Singer, Mervyn; Das, Abhishek; Arulkumaran, Nishkantha; , University College London Hospitals Critical Care Research Team (Frontiers in Immunology, 2025)
The Epidermal Growth Factor Receptor (EGFR) and its ligand, amphiregulin (AREG) are critical for epithelial cell proliferation but their important role in inflammation and infection is increasingly described. We recently discovered that the EGFR ligand, amphiregulin, could identify a cohort of infants with sepsis, even when CRP was low, identifying it as a potentially adjunctive biomarker for early infection. Its role in adult sepsis however, has yet to be delineated. We conducted a prospective observational study of 42 critically ill septic adult patients on the Intensive Care Unit, comparing serum amphiregulin levels and the frequencies of EGFR-expressing myeloid and lymphoid cells (using spectral flow cytometry) in sepsis survivors and non-survivors, and 20 healthy volunteers. We demonstrate, for the first time, the strong association between serum amphiregulin and in-hospital mortality (AUROC = 0.87). Moreover, we demonstrate that a higher frequency of circulating CD4+ and CD8+ lymphocytes express either the ligand (AREG) or receptor (EGFR) ex vivo, in sepsis, and expression of CD4+ lymphocyte EGFR was associated with several features of immunosuppression. Together, our data suggest that EGFR-signaling represents a novel candidate of T cell dysregulation in sepsis and warrants further investigation.